2013
DOI: 10.3356/jrr-12-00019.1
|View full text |Cite
|
Sign up to set email alerts
|

Bald Eagle and Golden Eagle Mortalities at Wind Energy Facilities in the Contiguous United States

Abstract: The wind power plant on the island of Smøla, western Norway, is currently the largest in Norway; it has 68 turbines with nominal capacity of 2-2.3 MW each, hub height of 70 m and rotor blade radius of 38-41 m,. It was constructed in two phases between 2001 and 2005. Approximately 60 White-tailed Eagle Haliaeetus albicilla territories are found in the whole Smøla archipelago. Before construction there were 13 Eagle pairs holding territories in the wind farm area and within 500 m of it, whereas in 2009 this was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 6 publications
(1 reference statement)
2
77
0
Order By: Relevance
“…Some recent studies and syntheses have indicated that Golden Eagles may be declining at least in some regions of North America (Kochert and Steenhof 2002, Hoffman and Smith 2003, Smith et al 2008, although recent reviews , Nielson et al 2014) have indicated that Golden Eagle populations are generally stable in the western U.S. Nielson et al (2016) suggested that this stability may be short-lived due in part to human-caused decline in habitats used by Golden Eagles. Anthropogenic landscape use and changes related to spread of invasive species (Kochert et al 1999), exurban expansion (Boeker 1974, Scott 1985, agricultural development (Beecham andKochert 1975, Craig et al 1986), recreation (Scott 1985, Watson 2010, Kochert et al 2002, Steenhof et al 2014, and energy development (Madders and Walker 2002, Rowland et al 2011, Pagel et al 2013 can negatively affect Golden Eagle reproduction and/or survival. Grasslands, sagebrush steppe, desert shrub, and other open landscapes provide important Golden Eagle habitat in the western United States and are undergoing especially rapid changes from human land use, altered fire regimes, and invasive species (Davies et al 2011).…”
Section: Amplitud De Dieta Y Reproducción En Aquila Chrysaetos En Relmentioning
confidence: 99%
“…Some recent studies and syntheses have indicated that Golden Eagles may be declining at least in some regions of North America (Kochert and Steenhof 2002, Hoffman and Smith 2003, Smith et al 2008, although recent reviews , Nielson et al 2014) have indicated that Golden Eagle populations are generally stable in the western U.S. Nielson et al (2016) suggested that this stability may be short-lived due in part to human-caused decline in habitats used by Golden Eagles. Anthropogenic landscape use and changes related to spread of invasive species (Kochert et al 1999), exurban expansion (Boeker 1974, Scott 1985, agricultural development (Beecham andKochert 1975, Craig et al 1986), recreation (Scott 1985, Watson 2010, Kochert et al 2002, Steenhof et al 2014, and energy development (Madders and Walker 2002, Rowland et al 2011, Pagel et al 2013 can negatively affect Golden Eagle reproduction and/or survival. Grasslands, sagebrush steppe, desert shrub, and other open landscapes provide important Golden Eagle habitat in the western United States and are undergoing especially rapid changes from human land use, altered fire regimes, and invasive species (Davies et al 2011).…”
Section: Amplitud De Dieta Y Reproducción En Aquila Chrysaetos En Relmentioning
confidence: 99%
“…Of specific concern are fatalities of species of conservation concern (e.g., Western Burrowing Owl [Athene cunicularia hypugaea]; Smallwood et al 2007) and species with small populations, delayed maturity, long lifespans, and low reproductive rates, for which even a few mortalities can have population-level effects (e.g., Golden Eagle [Aquila chrysaetos]: Lovich 2015; White-tailed Eagle [Haliaeetus albicilla]: Dahl et al 2012). While the number of birds affected is uncertain (Pagel et al 2013), estimates adjusted for searcher detection and scavenger removal suggest that between 140,000 and 328,000 birds are killed annually by collisions with turbines at wind energy facilities in the contiguous U.S. (Loss et al 2013). For songbirds in particular, fatalities at wind energy facilities in the U.S. and Canada are estimated to be between 134,000 and 230,000 annually (Erickson et al 2014 Morinha et al 2014), suggesting that the direct effects of wind energy facilities are of concern globally.…”
Section: Onshore Wind Energymentioning
confidence: 99%
“…Fish and Wildlife Service (U.S.F.W.S.) released ''Eagle Conservation Plan Guidance'' for proposed wind energy developments because of the risk of injury and mortality of eagles from collisions with wind turbines (Pagel et al 2013). One of the recommendations in this document is for compensatory mitigation actions that increase prey availability (U.S.F.W.S.…”
mentioning
confidence: 99%